Age-Specific Life Skills Education in School: A Systematic Review - Kirchhoff, Esther; Keller, Roger (Frontiers in Education, 2021)
Strengthening life skills is a popular approach for prevention and health promotion in schools. It aims to empower students to deal effectively with the demands of everyday life by improving self-regulation, making informed decisions, and building supportive social relationships. By addressing various health-related topics such as friendship, sexuality, violence, or substance use, life skills education has the potential not only to teach students how to act responsively regarding their health and well-being, but also to build a comprehensive understanding of the biological, psychological, and social factors influencing their individual development. However, little is known about whether the contents of life skills programs differ depending on student age, either in terms of the set of skills promoted or the influencing factors on health that are the focus. This systematic review addressed this gap by analyzing evaluated school-based life skills programs regarding age-specific targeted life skills, underlying theoretical frameworks, and effectiveness. The analysis, following the PRISMA guidelines, was based on longitudinal evaluation studies published between 2007 and 2020, which were retrieved from six electronic databases, and referred to eighteen programs. Results showed that programs were mostly implemented in adolescence and that the targeted life skills shifted from a more behavioral-affective focus in childhood to a broader set of life skills targeted in adolescence which emphasized social and sociocultural influencing factors on health. Little evidence was available on the effectiveness of the programs on life skills development. Ultimately, life skills education promotes health-related self-regulation, especially in adolescence. However, further research is needed to clarify how to achieve sustainable effects in the development of life skills, both in childhood and adolescence.